Small Cell Carcinoma of Prostate: A Case Report of a Patient With Concomitant Transitional Cell Cancer of the Bladder - Waiel Abusnina MD; Eric Yiman Auyoung MD; Mohammed Megri MD; Toni Pacioles MD (SAGE Publishing, 2018)
Small cell carcinomas (SCCs) are aggressive neoplasms commonly associated with a pulmonary origin. However, albeit rare, extrapulmonary SCC can occur in a variety of sites with an incidence in North America approximated to be 0.1% to 0.4%. Among these sites, approximately 10% of extrapulmonary SCC cases occur in the prostate and are associated with a poor mortality with a median survival of 10 months. Because of the rarity of the prostatic SCC, there is no formal treatment protocol. In this case report, we present a patient who was diagnosed with SCC in the prostate as primary origin. Adjuvant concurrent chemoradiotherapy was started, which he is tolerating so far. While the management of metastatic disease is well documented with the use of chemotherapy, specific data on nonmetastatic disease is lacking. As some studies suggest, a combined surgical and chemotherapeutic approach is helpful in localized disease. In our case, this approach has led to a good clinical outcome in a disease that does not usually allow such results.